Contribuição dos egressos da Escola Milton Santos para a promoção da agroecologia e desenvolvimento dos assentamentos de reforma agrária no Paraná - Toná, Nilciney (2016)
This dissertation investigated the actions of graduates of technical courses in Agroecology in settlements of the Agrarian Reform of Parana. This is a case study, qualitative research conducted with graduates of the School Milton Santos - EMS, located in Maringa-PR. The general objective was to evaluate the contribution of the graduates of EMS for promotion of Agroecology and development in settlements from Parana. It is verified, through literature and documental review, that the agrarian reform have been a place of action of Workers Movement Landless - MST to rethink about the development model of the field. For this demand technical training in Agroecology for young settlers, implementing formal technical courses and structuring Training Schools in Agroecology, among them the School Milton Santos since 2002. Has developed training partnerships with various institutions, forming four classes in technical courses in Agroecology, with students from various settlements and regions of the State. The analysis of interviews with students and leaders of the settlements and documentary research has found that most graduates maintain bond and contributing objectively and subjectively differentiated from agribusiness production model for the settlements through educational, organizational and productive actions for consumption and income of families. The limits do not concern only the formation offered in courses, but the contradictions that involve the settlements and dispute of models of development in these territories.